Development of the chromatographic medium for the affinity isolation of the recombinant hIFN-β1b based on immobilized single-chain antibodies - Pokholenko, Ia.O.; Gorbatiuk, O.B.; Okunev, O.V.; Irodov, D.M.; Degtiarova, M.I.; Palivoda, O.G.; Kordium, V.A. (Вiopolymers and Cell, 2015)
Aim. The development of a laboratory method for the production of immunoaffinity chromatography medium for the purification of the recombinant human IFN-β1b. Methods. A gene of the chimeric protein ScFvbINF-CBD was constructed using the DNA sequences encoding ScFv specific to hIFN-β1b and the cellulose-binding domain (CBD) of Clostridium thermocellum. The developed chimeric protein was expressed in Escherichia coli cells. The target protein was obtained in soluble, functionally active form by its renaturation from the bacterial inclusion bodies in vitro. The ScFvbINF-CBD was immobilized on a chitin carrier. Results. The introduction of CBD by gene engineering techniques enabled the oriented non-covalent immobilization of ScFvbINF-CBD on chromatographic matrix. The developed immunoaffinity medium allowed isolating the rhIFN-β1b from the complex mixture, after its renaturation from the inclusion bodies, with more than 89 % purity. Conclusion. The designed immunoaffinity medium provides isolating the rhIFN-β1b from the complex protein mixtures. Мета. Розробити лабораторний метод створення імуноафінного хроматографічного сорбенту для виділення та очищення рекомбінантного IFN-β1b людини. Методи. Використовуючи послідовності ДНК, які кодують ScFv специфічні до hIFN-β1b, та целюлозозв’язувальний домен (CBD) Clostridium thermocellum, створено ген химерного протеїну ScFvbINF-CBD. Проведено експресію створеного химерного протеїну в клітинах Escherichia coli. Цільовий білок одержували у розчинній, функціонально активній формі шляхом ренатурації з бактеріальних тілець включення in vitro. ScFvbINF-CBD іммобілізували на хітиновому носії. Результати. Введення CBD до складу химерного білка забезпечує орієнтовану, не ковалентну іммобілізацію ScFvbINF-CBD на хроматографічній матриці. За допомогою створеного імуноафінного сорбенту було виділено rhIFN-β1b зі складної суміші білків, одержаної після його ренатурації з тілець включення, з чистотою більше ніж 89 %. Висновки. Створений імуноафінний хроматографічний сорбент дозволяє виділяти рекомбінантний IFN-β1b людини зі складних сумішей білків. Цель. Разработать лабораторный метод создания иммуноаффинного хроматографического сорбента для выделения и очистки рекомбинантного IFN-β1b человека. Методы. Используя последовательности ДНК, кодирующие ScFv специфичные к hIFN-β1b, и целлюлозосвязывающий домен (CBD) Clostridium thermocellum, создан ген химерного белка ScFvbINF-CBD. Проведена экспрессия созданного химерного белка в клетках Escherichia coli. Целевой белок получали в растворимой, функционально активной форме путем ренатурации из бактериальных телец включения in vitro. ScFvbINF-CBD иммобилизовали на хитиновом носителе. Результаты. Введение CBD в состав химерного белка обеспечивает ориентированную не ковалентную иммобилизацию ScFvbINF-CBD на хроматографической матрице. С помощью созданного иммуносорбента был выделен rhIFN-β1b из сложной смеси белков, полученной после его ренатурации из телец включения, с чистотой более 89 %. Выводы. Созданный иммуноаффинный хроматографический сорбент позволяет выделять рекомбинатный IFN-β1b человека из сложных белковых смесей.